Islamic Law and Women’s Rights in Indonesia: A Case of Regional Sharia Legislation - Nur Hidayah (AHKAM : Jurnal Ilmu Syariah, 2019)
Under Indonesia decentralization policy which grants regional governments more authority to manage their own local affairs, some predominantly Muslim regions have passed sharia regional legislation on the ground of popular aspirations and local particularities. It has raised a question of whether the regional autonomy will provide new opportunities for women to promote their rights within closer local governments or it will inadvertently restrain women’s advancement. Answering the question, this paper will firstly discuss the decentralization policy that opens up the opportunity for regional sharia legislation. Then it will examine the legal substance of the so-called perda (sharia-based bylaws) and their impacts on women’s rights. Being influenced by conservative sharia interpretation laden with patriarchal values, these sharia-based bylaws discriminate against women, as reflected in their stipulations regarding women’s familial and social roles, dress codes, curfews, public segregation, and prostitution. The rise of Islamic conservatism during Indonesian democratization and the lack of gender perspectives in the decentralization policies have contributed to such discriminatory regional sharia legislation. Therefore there is an urgent need for religious reform as well as more sensitive gender policies in implementing the decentralization so that the sharia and regional autonomy can go hand in hand to support women’s rights promotion. Kebijakan desentralisasi memberi banyak wewenang untuk mengelola urusan lokal daerah  sendiri. Beberapa provinsi dan kabupaten yang mayoritas Muslim telah mengeluarkan peraturan daerah (Perda) syariah berdasarkan aspirasi rakyat dan kekhasan lokal. Fenomena ini telah menimbulkan pertanyaan apakah otonomi daerah akan membuka peluang baru bagi perempuan untuk mempromosikan hak-hak mereka di daerahnya sendiri atau akan menghambat kemajuannya. Untuk menjawab pertanyaan semacam itu, penelitian ini pertama-tama akan membahas kebijakan desentralisasi yang membuka peluang bagi legislasi syariah regional. Kemudian,  pemeriksaan substansi hukum apa yang disebut perda syariah tersebut dan dampaknya terhadap hak-hak perempuan. Temuan penelitian ini memperlihatkan adanya pengaruh interpretasi syariah konservatif yang sarat dengan nilai-nilai patriarki sehingga peraturan berbasis syariah ini mendiskriminasi perempuan, sebagaimana tercermin dalam ketentuan mereka mengenai peran keluarga dan sosial perempuan, aturan berpakaian, jam malam, segregasi publik, dan prostitusi. Munculnya konservatisme Islam selama demokratisasi Indonesia dan kurangnya perspektif gender dalam kebijakan desentralisasi baik di tingkat pemerintah daerah dan masyarakat telah berkontribusi terhadap undang-undang syariah regional yang diskriminatif ini. Oleh karena itu, ada kebutuhan mendesak untuk mereformasi interpretasi agama yang konservatif serta kebijakan jender yang lebih sensitif dalam menerapkan desentralisasi sehingga syariah dan otonomi daerah dapat berjalan beriringan untuk bersama-sama mendukung penguatan hak-hak perempuan.